PESTILENCE, INSANITY, AND TREES - Harris, John M. (John Malcolm), 1948- (ABINGDON)
1 online resource
Keywords: This is the first full-length biography of New York surgeon and social activist Stephen Smith (1823-1922), who was appointed to fifty years of public service by three mayors, seven governors, and two U.S. presidents. The book presents the complex life of Stephen Smith, a consistent figure in the history of public health, mental health, housing reform in New York, and even urban reforestation. Utilizing Smith's writings, public records, and recently discovered personal correspondence, this research shows how Smith succeeded where others failed. It also acknowledges that Smith was unsuccessful in convincing his fellow professionals to fight for a cabinet level public health department or to resist the rise of custodial care for the mentally impaired. Given Smith's many accomplishments, the book asks us to consider if what stopped him stops us, highlighting the relevance of Smith's story to contemporary debates. Pestilence, Insanity, and Trees is a readable and well-documented narrative and a resource for students and scholars, filling gaps in the history of American medicine, public health, mental health, and New York social reform.